Cytogenetic studies in South American species of Serjania (Sapindaceae: Paullinieae) - Urdampilleta, Juan Domingo (2012)
Serjania Mill. (Paullinieae) is considered the most important neotropical genus of Sapindaceae due to species number and its widespread distribution. In this study, 14 species belonging to three sections were analyzed using conventional staining, C/ CMA/DAPI banding, and fluorescence in situ hybridization (FISH) with a 18S-5.8S-26S rDNA probe. New chromosome counts are reported for Serjania crassifolia, Serjania platycarpa, and Serjania regnellii, all with 2n¼24, which is remarkably constant for Serjania. The karyotypes are moderately asymmetric, and variations observed in A1 and A2 indices show resemblances between S. platycarpa, Serjania hebecarpa, and S. crassifolia, and between Serjania communis, Serjania gracilis, and S. regnellii. The banding pattern was homogeneous in Serjania. C/DAPI bands (AT-rich sites) were not clearly evidenced, but changes in the number and position of GC-rich sites (CMA bands) were observed. These segments were associated with 18S-5.8S-26S rDNA sites. The significance of the results is discussed in relation to chromosomal data available for the genus and in regard to the infrageneric treatment of Serjania.